Some tardigrades from Siberia (Russia, Baikal region) with a description of Macrobiotus garynahi sp. nov. (Eutardigrada: Macrobiotidae: richtersi group) - Kaczmarek, Łukasz; Michalczyk, Łukasz; Diduszko, Dawid (Zootaxa, 2005)
A new species, Macrobiotus garynahi sp. nov. is described from a lichen sample collected in the Baikal region (Russia). The new species belongs to the richtersi group and it is most similar to M. vanescens Pilato et al., 1991 and M. alekseevi Tumanov, 2005. The new species differs from M. vanescens by the presence of more evident microplacoid, different shape of egg processes and shorter claws. M. garynahi sp. nov. differs from M. alekseevi by the presence of granulation on all legs, different oral cavity armature, generally larger body size and different shape of egg processes. Also in this paper, another seven Tardigrada species are reported from Siberia (Russia). One of them, Macrobiotus crenatus Maucci is new to this region and this is also the first record of this species other than Greenland (type locality).